Torsion of a giant epididymal cyst in a pediatric patient: a rare cause of acute scrotal pain—case report and literature review - Zhanghuang, Chenghao; Li, Jinrong; Long, Na; Duan, Qiong; Ji, Fengming; Xie, Yucheng; Yang, Zhen; Yan, Bing (Frontiers in Pediatrics, 2025)
Torsion of an enlarged epididymal cyst (EC) represents an uncommon yet critical differential diagnosis in acute scrotal emergencies. Large ECs, particularly those localized to the epididymal head, demonstrate diminished anatomical stability due to their superior positioning and increased mobility, rendering them susceptible to torsion under predisposing conditions. This mechanical disruption precipitates elevated intracystic pressure, compromised vascular perfusion, and subsequent infective complications, necessitating urgent surgical intervention. We present a case of a 12-year-old male who presented with left scrotal swelling and pain persisting for 48 h. Initial clinical evaluation suggested spermatic cord torsion concomitant with hydrocele, prompting emergency exploration. Intraoperative findings unexpectedly revealed a torsioned giant cyst (5.2 × 3.8 cm) originating from the left epididymal head. Successful detorsion followed by complete cyst excision was performed while preserving testicular integrity and epididymal architecture. Histopathological analysis confirmed the lesion as a mesonephric duct remnant cyst.